Autoantibodies in relatives of celiac disease patients: a follow-up of 6-10 years - Nass,Flávia Raphaela (2012)
CONTEXT: Autoimmune diseases are 3 to 10 times more frequently in patients with celiac disease and their relatives than in the general population. OBJECTIVE: To investigate a broad spectrum of autoantibodies in celiac disease relatives from Southern Brazil, in a serological follow-up of 6-10 years, aiming to associate with other autoimmune diseases, degree of parentage, demographic and clinical data. METHODS: Serum samples of 233 relatives were analyzed in two different phases: n = 186 in phase I (1997-2000) and n = 138 (being 91 = follow-up group and 47 = newly tested) in phase II (2006-2007). As controls, 100 unrelated individuals were evaluated. Autoantibodies to smooth muscle, mitochondrial, liver-kidney microssome, parietal cell and thyroid microssome were tested by indirect immunofluorescence. RESULTS: A significant increase of autoantibodies, in both phases, was observed in the relatives when compared to the non-relatives (P = 0.0064), specifically to anti-thyroid microssome and anti-parietal cell. In both phases, the female/male proportion of autoantibodies was of 4:1 to 3:1 (P<0.041). The frequency of autoantibodies amongst 1st and 2nd degree relatives was 11.8% and 9.68% in phase I and 4% and 6.67% in phase II. CONCLUSION: Celiac disease relatives presented other autoantibodies and serological screening is a useful instrument for identifying autoimmune diseases along the years.